2008
DOI: 10.3174/ajnr.a1130
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Differentiation of Aerobic Brain Abscesses and Necrotic Glioblastomas Multiforme Using Proton MR Spectroscopic Imaging

Abstract: BACKGROUND AND PURPOSE:Abscesses caused by aerobic bacteria (aerobic abscesses) can simulate intracranial glioblastomas multiforme (GBMs) in MR imaging appearance and single voxel (SV) proton MR spectroscopy of the central cavity. The purpose of our study was to determine whether MR spectroscopic imaging (SI) can be used to differentiate aerobic abscesses from GBMs. Our hypothesis was that metabolite levels of choline (Cho) are decreased in the ring-enhancing portion of abscesses compared with GBMs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 31 publications
2
29
0
1
Order By: Relevance
“…However, the middle part of glioblastomas had in general lower values of tNAA/tCr compared to its solid or peritumoral regions, they did not differ significantly from each other. This indicated an infiltrating character of the tumor cells, which is in compliance with the published characteristics of glioblastomas (Lai et al 2008;Law 2009;Wright et al 2009). Using this clinically feasible 1 H MRSI evaluated at 1.5 Tesla it was possible to demonstrate high heterogeneity of glioblastomas, with necrotic middle part, highly proliferating solid part, metabolically influenced surrounding tissue with infiltrating tumorous cells (Fig.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…However, the middle part of glioblastomas had in general lower values of tNAA/tCr compared to its solid or peritumoral regions, they did not differ significantly from each other. This indicated an infiltrating character of the tumor cells, which is in compliance with the published characteristics of glioblastomas (Lai et al 2008;Law 2009;Wright et al 2009). Using this clinically feasible 1 H MRSI evaluated at 1.5 Tesla it was possible to demonstrate high heterogeneity of glioblastomas, with necrotic middle part, highly proliferating solid part, metabolically influenced surrounding tissue with infiltrating tumorous cells (Fig.…”
Section: Discussionsupporting
confidence: 67%
“…There is a theory suggesting that due to the growing tumor the neovasculature could not sufficiently supply the more distant cells, resulting in hypoxic or almost necrotic regions, particularly in the central part of tumors (Lupo et al 2007;Garett and Grisham 2008;Ganapathy et al 2009). As a consequence spectroscopically detectable lipids could be present in these regions (Lai et al 2008;Delikatny et al 2011). In this study increased value of lip/Lac ratio was found suggesting the central tumor necrosis.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Various MRI sequences were used including GRE and DWI, however, main limitation of this study was lack of use of advanced MRI tools like perfusion weighted imaging and MR spectroscopy that can be of help for accurate tissue characterisation. (17) CONCLUSION MRI proves to be a valuable modality of imaging in accurately evaluating the morphologic distribution of various intra-and extra-axial tumours in the posterior fossa.…”
Section: Discussionmentioning
confidence: 99%